Effect of carbon and nitrogen sources on lipase production by bacterial isolate LJK2(1)2 - Nur Far'ain Mohamad Termezai (2015)
Lipases are very important enzyme that mostly applied in many industries like food, pharmaceutical, pulp and paper and also detergent industries. In this study, bacterial lipase isolates, LJK2(1)2 was collected from UMK laboratory. The optimization of fermentation medium for lipase production was carried out. The effects of nutritional requirements like carbon sources, organic nitrogen sources and inorganic nitrogen sources on lipase were investigated. The lipase activity were identified by titration method. As a result, sucrose (3.78 U/ml) was the best carbon sources while yeast extract (10.883 U/m1) was the best organic nitrogen source that showed the highest lipase production. The inorganic nitrogen sources were compared between the inorganic nitrogen source with or without the presence of organic nitrogen source. The combination of urea and yeast extract (19.12 U/ml) were better nitrogen sources for the maximum lipase production.